2015
DOI: 10.1007/jhep05(2015)064
|View full text |Cite
|
Sign up to set email alerts
|

ABJM theory with mass and FI deformations and quantum phase transitions

Abstract: The phase structure of ABJM theory with mass m deformation and nonvanishing Fayet-Iliopoulos (FI) parameter, ζ, is studied through the use of localisation on S 3 . The partition function of the theory then reduces to a matrix integral, which, in the large N limit and at large sphere radius, is exactly computed by a saddle-point approximation. When the couplings are analytically continued to real values, the phase diagram of the model becomes immensely rich, with an infinite series of third-order phase transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 50 publications
(191 reference statements)
7
41
0
Order By: Relevance
“…This averaging results in the constant eigenvalue distribution obtained in [8]. Similar behavior was obtained for the solutions containing resonances in the mass-deformed ABJM theory [32,33] and 4D N = 2 * theory [22].…”
Section: The Strong Coupling Limitsupporting
confidence: 74%
See 1 more Smart Citation
“…This averaging results in the constant eigenvalue distribution obtained in [8]. Similar behavior was obtained for the solutions containing resonances in the mass-deformed ABJM theory [32,33] and 4D N = 2 * theory [22].…”
Section: The Strong Coupling Limitsupporting
confidence: 74%
“…Finally, as mentioned in the introduction, studies of the decompactification limit in different 3D and 4D theories revealed interesting phase structure of these theories. For instance, phase transitions were found in 3D Chern-Simons coupled to the massive fundamental hypermultiplet [30], in 4D N = 2 super-QCD with massive quarks in the Veneziano limit [24], in mass-deformed ABJM theory [32,33] and finally in 4D N = 2 * SYM theory [22]. In each case theory was considered in the decompactification limit and it was shown that in the finite volume phase transitions disappear.…”
Section: Jhep07(2015)004mentioning
confidence: 99%
“…Here we use a slightly more general procedure than [13], which will generalize to the case with insertion of Fayet-Iliopoulos deformation. Based on previous results [13,17] we assume a one-cut solution for ρ, supported in some closed interval [−A, B]. In the present case with opposite masses and equal number of hypermultiplets associated to each mass, the support will turn out to be symmetric, B = A.…”
Section: Eigenvalue Distributionmentioning
confidence: 99%
“…See also [49][50][51]. Though the setup is different from ours, where the mABJM theory is defined on R 2,1 , it is intriguing to investigate the gravity dual for our case in the large mass region and compare the results with those of mABJM theory on S 3 .…”
Section: Jhep04(2017)104mentioning
confidence: 92%